Prophylaxis end treatment of vascular complications after liver transplantation - S. V. Zhuravel; O. I. Andreytseva; L. V. Donova; K. R. Dzhagraev; A. V. Chzhao (Трансплантология (Москва), 2018)
The study analyzes the reasons for the development of vascular complications, prevention and treatment after liver transplantation. In a retrospective study enrolled 206 patients who had undergone 214 orthotopic liver transplantation (OLT). Vascular complications has diagnosed in 18 (8.4 %) patients in postoperative period. A relatively low incidence of hepatic artery thrombosis (HAT) had seen in our study. Low molecular weight heparin (LMWH) plays an important role in the prevention of thrombosis. Doppler ultrasonography is a convenient and efficient method for detecting posttransplant complications and plays an important role in guiding treatment. Early diagnosis of these complications allows to decide on the tactics of the patients and to determine indications for emergency surgical revascularization and save the graft.